Review of fruit cork spot disorder of Asian pear (Pyrus spp.) - Zhang, Xiaozhen; Cui, Zhenhua (Frontiers in Plant Science, 2023)
Cork spot disorder has affected the fruit of Asian pear (Pyrus spp.) since the 1990s and has become increasingly serious in recent years. The cultivars and areas affected by this disorder have been increasing annually. The commodity value of affected fruit is greatly decreased, resulting in severe economic losses. Cork spot disorder of pear fruit is a physiological disorder and the factors responsible are relatively complex. Research on the cause of cork spot disorder is still at an early stage and, thus, further investigations are needed to elucidate the underlying mechanism of the disorder. In this review, current knowledge of the factors associated with the incidence of cork spot disorder in Asian pear fruit is summarized, including fruit growth and development, fruit nutrient status, and environmental factors. Potential preventive measures and priorities for future research are outlined.